2017
DOI: 10.1021/acs.jnatprod.6b00889
|View full text |Cite
|
Sign up to set email alerts
|

Talarazines A–E: Noncytotoxic Iron(III) Chelators from an Australian Mud Dauber Wasp-Associated Fungus, Talaromyces sp. (CMB-W045)

Abstract: Chemical analysis of an Australian mud dauber wasp-associated fungus, Talaromyces sp. (CMB-W045), yielded five new coprogen siderophores, talarazines A-E (1-5), together with dimerumic acid (6), desferricoprogen (7), and elutherazine B (8). Structures inclusive of absolute configuration were assigned on the basis of detailed spectroscopic analysis and application of the C Marfey's method. We report on the noncytotoxic Fe(III) chelation properties of 1-8 and demonstrate that biosynthesis is regulated by availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…This effect could be reversed by adding supplementary Fe(III) to jasmine rice cultivations (suppressing talarazine biosynthesis), or adding the Fe(III) chelator EDTA to red rice cultivations (activating talarazine biosynthesis). That the biosynthesis of the siderophore talarazines is linked to the availability of Fe(III) serves to illustrate that all rice media are not the same, and that Fe(III) is a transcriptional activator [38]. C. Red versus Jasmine Rice: When grown on jasmine rice media known to be deficient in Fe(III), Talaromyces sp.…”
Section: Cultivation Profiling 61 Media Matrixmentioning
confidence: 99%
“…This effect could be reversed by adding supplementary Fe(III) to jasmine rice cultivations (suppressing talarazine biosynthesis), or adding the Fe(III) chelator EDTA to red rice cultivations (activating talarazine biosynthesis). That the biosynthesis of the siderophore talarazines is linked to the availability of Fe(III) serves to illustrate that all rice media are not the same, and that Fe(III) is a transcriptional activator [38]. C. Red versus Jasmine Rice: When grown on jasmine rice media known to be deficient in Fe(III), Talaromyces sp.…”
Section: Cultivation Profiling 61 Media Matrixmentioning
confidence: 99%
“…Besides, the bare SPIONs can be degraded via the body metabolism causing an overload of iron ions in tissues. Inspired by reports that used Fe 3 O 4 NPs to selectively adsorb siderophores as a microbial chelator with high affinity 26 , 27 , we demonstrated the capability of magnetic NPs chelated with purified bacterial PVD. Previous studies revealed that SPION can be conjugated with any drugs and/or natural compounds containing sulfhydryl (-SH), amine (-NH 2 ), phosphate (PO 4 3- ), hydroxyl (-OH), and carboxyl (-COOH) groups or their combinations 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of two Egyptian reports concerning T. funiculosus from dead larvae and pupae of the vegetable leafminer (Liriomyza sativae) (Diptera, Agromyzidae) [26] and T. pinophilus from an unspecified stage of the red palm weevil (Rhynchophorus ferrugineus) (Coleoptera, Curculionidae) [30], as well as of Talaromyces sp. from an unidentified mud dauber wasp in Australia [42], Talaromyces versatilis from dead individuals of the giant honey bee (Apis dorsata) (Hymenoptera, Apidae) in Sri Lanka [52] and T. variabilis from adults of Diabrotica sp. (Coleoptera, Chrysomelidae) and Neomyopites sp.…”
Section: Occurrence Of Talaromyces Spp As Insect Associatesmentioning
confidence: 99%